Tree Canopies Influence Ground Level Atmospheric Electrical and Biogeochemical Variability - Hunting, Ellard R.; England, Sam J.; Robert, Daniel (Frontiers in Earth Science, 2021)
Static electric fields in the atmosphere are increasingly recognized as interacting with various organisms over several levels of biological organization. Recently, a link between atmospheric electrical variations and biogeochemical processes has been established in the context of open fields, yet biological structures like trees produce substantial alterations in atmospheric electric properties. Here, we assess whether these structural changes affect the dynamics of the electrical landscape and its relation to geochemical processes. To this end, we theoretically assess how trees alter their surrounding electric fields and empirically compare the temporal dynamics of atmospheric potential gradients, positive ions in the near-ground level atmosphere and soil electrochemical properties in an open field and under a tree. The developed model of electric fields around trees provides insight into the extent to which trees shield underlying electric landscape, revealing that a substantial increase in atmospheric potential gradient only marginally affects the electric field under the canopy. We further show that soil electrochemical properties are tied to temporal dynamics of positive ions in the near-ground level atmosphere, and that the presence of a tree reduces the temporal variability in both ground level positive ions concentrations and soil redox potential. This suggests that a tree can alter of the temporal variability in atmospheric electricity and soil electro-chemistry, thereby likely indirectly influencing soil microorganisms and processes as well as electro-sensitive organisms that perceive and utilize atmospheric electric fields.